THE SECURITY SYSTEM OF THE REPUBLIC OF NORTH MACEDONIA AND THE COVID-19 PANDEMICS - Nikolovski, Marjan; Gjurovski, Marjan (Horizons - International Scientific Journal, 2021)
Today we live in a time characterized by enormous development of science, technique and technology. That fact, in itself, implies certain socio-economic changes that were not present in the past. If in the past, the greatest danger that threatened humanity was the wars, which were characterized by the use of various artillery, offensive and other weapons, today we are definitely moving to another, more advanced cultural-historical-civilizational stage of society, as well as of man as a social being. At this stage, classical warfare is no longer the biggest threat to the security of nation states, but on the contrary, hybrid, asymmetric threats, organized crime, corruption, computer fraud, environmental threats and of course new types of epidemic threats.